PUBLIC PREFERENCES ON FACTORS AFFECTING MAQASHID SHARIAH-BASED HEALTH INSURANCE SERVICES IN ACEH PROVINCE - Muhammad Zulhilmi; Winny Dian Safitri; Nadlia Ariyati (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2023)
Health development is a development effort in the health sector that aims to achieve optimal health status. The Aceh government, through special autonomy rights, carries out the development of the health sector through health insurance which is named the sharia-based Aceh Health Insurance (JKA) managed by the Social Security Administration (BPJS) to meet the health needs of all Acehnese people so that the objectives of Maqashid shariah are achieved, namely benefit. This study aims to determine the community's preference for factors that affect Maqasid Shariah-based health services in Aceh. This research approach is quantitative, using the method of statistical analysis of the structural equation model based on partial least squares. This study indicates a statistically significant effect on the variables of socialization intensity, accessibility of information, availability of facilities and infrastructure for the services of health insurance participants at a significant level of 10%. Based on the Acehnese people's preferences, both facilities and infrastructure are important factor in running health insurance services.